In Military Units and Organizations of the NBC Protection Troops of the Armed Forces of the Russian Federation Solemn Events Are Held to Consecrate the Icon of the Patron Saint of the NBC Protection Troops - Н. П. Соляник (Вестник войск РХБ защиты, 2020)
.